DAYA HAMBAT MINYAK ATSIRI DAN EKSTRAK LIMBAH SISA DESTILASI RIMPANG KUNIR PUTIH (Kaempferia rotunda L.) TERHADAP PERTUMBUHAN Candida albicans ATCC 10231 - Christina Astutiningsih; Ratih Octaviani; Sri Suratiningsih (Sanata Dharma University, 2014)
Abstract: White turmeric rhizome contains alkaloid, saponin, flavonoid, polifenol, and essentialoils. The purpose of this research is to determine the antifungal activity of essensial oil andresidual destillation of white turmeric rhizome against Candida albicans. Essential oils of whiteturmeric rhizome isolated by steam distillation method, the extraction of waste with soxhletasimethod. Antifungal activities were investigated by the paper disc method method. The test resultsshowed antifungal activity of essential oil of white turmeric rhizome in different concentrations(0.75, 1, 2, and 2.25%) were 0.0 ; 0.736 ; 0.894 ; 1.041 cm. The antifungal activities of theresidual distillation of extract (2.25, 2.5, 3, and 4%) were 0.0, 0.674, 0.743 and 0.874 cm. Therewas a difference of the zone of inhibition of Candida albicans growth between essential oils andresidual distillation of white turmeric rhizome.Keywords: White turmeric, Candida albicans, essential oils, extract of waste, inhibiton.